Pengaruh Budaya Organisasi Dan Pengembangan Karir Terhadap Kinerja Guru Di SMA Darussalam Poris Kota Tangerang - Siti Rohmaniah; R.A Kadarmanta (CV. KAMPUSA AKADEMIK PUBLISING, 2026)
Abstract. This study aims to examine and analyze the effect of organizational culture and career development on teacher performance at SMA Darussalam Poris, Tangerang City. The research employed a quantitative approach using a survey method. The population consisted of all teachers totaling 35 respondents using a saturated sampling technique. Data were collected through questionnaires that had been tested for validity and reliability and were analyzed using the Statistical Package for the Social Sciences (SPSS) The results show that partially, organizational culture has a positive and significant effect on teacher performance with a t-value of 3.289 and a significance level of 0.002 (<0.05). Career development also has a positive and significant effect on teacher performance with a t-value of 2.658 and a significance level of 0.012 (<0.05). Simultaneously, organizational culture and career development have a significant effect on teacher performance with an F-value of 226.591 and a significance level of 0.000 (<0.05). The coefficient of determination (R²) of 0.934 indicates that 93.4% of the variation in teacher performance can be explained by these two variables, while the remaining 6.6% is influenced by other factors outside the study.In conclusion, a strong organizational culture and a well-planned career development system play a crucial role in improving teacher performance. Therefore, schools are encouraged to strengthen organizational values and enhance career development programs to support optimal teacher performance.